y.y'' - ( y' )^2 = 0 . This Eq. can be written as :
yy'' = (y')^2 or y''/y' = y'/y.
Integrating the two sides, we get:
ln(y') =ln(y) + ln(c), where c or ln (c) is a constant.
This leads to : y' =c y. Now we rewrite it as:
y'/y = c. integrating it again, we get:
ln(y) = cx + d, where d is a constant.
This leads to y= A exp(cx), where A=exp(d).
Answer: y = A exp( cx). Should we check the answer?
y'= Ac exp(cx) and y'' = A c^2 exp(cx),
Then y.y'' - ( y' )^2
=A^2 c^2 exp(2cx) -A^2 c^2 exp(2cx) = 0.
So the given Eq. is satisfied.Good
2007-01-16 08:50:03
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
For the best answers, search on this site https://shorturl.im/avZUM
One solution is y = cosh x. I let you find the others =) edit differentiate you get y'y'' + yy''' - 2y'y'' = 0 so yy''' = y'y'' or y'/y = y'''/y''. This gives ln y'' = ln y + C or y'' = e^C * y. You know solutions to such equations are of the form y = a cosh ut + b sinh u t with u^2 = e^C. Just plug into your equation and see what it gives for a,b,u. Can't be hard.
2016-04-10 07:26:09
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
Yy Y 2 0
2016-11-01 23:29:53
·
answer #3
·
answered by ? 4
·
0⤊
0⤋
it looks like y'/y is constant right? So ln y = Cx + C' or y= K e^{ax}
2007-01-16 08:24:53
·
answer #4
·
answered by gianlino 7
·
1⤊
0⤋
ugg!
You can tell all the kids just got out of school! They're asking us all to do their homework!!!
2007-01-16 08:24:11
·
answer #5
·
answered by Coltsgal 5
·
2⤊
3⤋
I believe the answer is (_)_)////////////////////////D
2007-01-16 08:24:59
·
answer #6
·
answered by C = JD 5
·
0⤊
2⤋